Carboxylato-Pillar[6]arene-Based Fluorescent Indicator Displacement Assays for Caffeine Sensing - Duan, Qunpeng; Xing, Yibo; Guo, Kainan (Frontiers in Chemistry, 2021)
In the present work, we have developed a new indicator displacement system based on pillararene for anionic water-soluble carboxylato pillar[6]arene (WP6) and aromatic fluorescent dye safranine T (ST). A large fluorescence enhancement and colour change of ST were observed after complexation with electron-rich cavity in WP6 because of host-guest twisted intramolecular charge-transfer interactions. The constructed pillararene-indicator displacement system can be applied for caffeine selective detection in water.